Optimalisasi Pembelajaran Jarak Jauh dalam Pelatihan UMKM untuk Peningkatan Kemampuan Pelaku UMKM di Era Ekonomi Digital - Sidabutar, Victor TP (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
To prevent the virus transmission, Covid 19 Pandemic forced learning activities shifted from face to face to distance learning. Elements involved in the education and training of micro, small and medium enterprises, such as Education and Training institutions, teachers and participants are forced to adapt not only due to the pandemic but also to face the changing world economy into a digital economy due to the rapid evolution and increasing use of information and communication technology. communication. Indonesia is currently in 11 countries in Asia Pacific that use cellular operators that are experiencing rapid development in mobile collaborative platforms as an indicator of improving information and communication technology, especially in internet and cellular usage. For this reason, education and training institutions, teachers and participants are required to be able to take advantage of technological developments in the implementation of distance learning such as the use of the internet, Learning Management Systems and other supporting tools to support digital economic growth in Indonesia. This study aims to analyze and optimize the supporting factors for the development of Distance Learning related to the development of education and training during the pandemic.